Penyidikan Dan Penuntutan Tindak Pidana Penyelundupan Manusia di Indonesia - Maulida, Asri; Retno Murni, R. A. (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 04, September 2013, 2013)
As one of the transnational crime of human smuggling caused problems for thegovernment and for Indonesia. But now a days less than two decades the issue of humansmuggling become strategic environment in Indonesia and Asia region encourages humantrafficking crimes to be one type of transnational crime which is the most attention. In this casethe crime of human smuggling different from human trafficking. There for the parties whoinvolved in this case either the government, the police, the Attorney General and even the peopleof Indonesia should interceptions in the crime under this attention. Regarding the legality of thecrime of human trafficking, it seems political Indonesian law requires that it is not only handleby Immigration ranks but also handled by the police. Finally, the police have the responsibilityto conduct the investigation, then investigation by the Attorney General's Police formed a taskforce is will be deal with the Transnational Crime in the case of prosecutions.
Keywords: Investigation, Prosecution, Smuggling